PEMBUATAN LABEL/FILM INDIKATOR WARNA DENGAN PEWARNA ALAMI DAN SINTETIS - Endang Warsiki dan Citra Dewi Wahyono Putri (E-Jurnal Agro-Industri Indonesia) (E-jurnal Agro-Industri Indonesia, 2012)
ABSTRAK   The development of colored label indicator is increasingly necessary to ensure food safety with a rapid method to evaluating historical real-time of the freshness of the product. The objective of this research is to design labels/film color indicator with natural and synthetic dyes. In this study, the label/film indicators was made of chitosan as a film base and natural dyes of rosella flower, bit fruit and red spinach leaf extract as dyes. This indicator label sware compared with labels made of synthetic dyes. Evaluation the performance of the label in color changes during storage as visual looking was tested  The results showed that natural dyes are very sensitive to temperature, thus it is not appropriate if in the film making, it involves a process that uses high temperatures. Unfortunately, in general, chitosan film typically used a temperature of 70oC to disolve and homogenize the flour of chitosan. Furthermore, natural dyes are also sensitive to acid. As a result, the addition of acetate acid in the chitosan film is undesirable on the filming. Process synthetic dyes provide constant color film. The changing of color in the films with synthetic dyes can be occured due to changes in pH. Therefore, this film/label is very suitable to be applied for products which is decreased in pH if it is deterioration, such as fruits or dairy product.   Keywords : Film/label, color indicator, chitosan, natural dye, synthetic dye